Measurements of the center-of-mass energies of collisions at BESIII *Supported in part by National Key Research and Development Program of China (2020YFA0406300, 2020YFA0406400); National Natural Science Foundation of China (NSFC) (11625523, 11635010, 11735014, 11822506, 11835012, 11935015, 11935016, 11935018, 11961141012); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1732263, U1832207); CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH003, QYZDJ-SSW-SLH040); 100 Talents Program of CAS; INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (758462); European Union Horizon 2020 research and innovation programme (Marie Sklodowska-Curie grant agreement No 894790); German Research Foundation DFG (443159800), Collaborative Research Center CRC 1044, FOR 2359, FOR 2359, GRK 214; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (DPT2006K-120470); National Science and Technology fund; Olle Engkvist Foundation (200-0605); STFC (United Kingdom); The Knut and Alice Wallenberg Foundation (Sweden) (2016.0157); The Royal Society, UK (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0012069). (October 2021) - Ablikim, M.; Achasov, M. N.; Adlarson, P.; Ahmed, S.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An, M. R.; An, Q.; Bai, X. H.; Bai, Y.; Bakina, O.; et al.
Abstract: During the 2016-17 and 2018-19 running periods, the BESIII experiment collected 7.5 fb of collision data at center-of-mass energies ranging from 4.13 to 4.44 GeV. These data samples are primarily used for the study of excited charmonium and charmoniumlike states. By analyzing the di-muon process, we measure the center-of-mass energies of the data samples with a precision of 0.6 MeV. Through a run-by-run study, we find that the center-of-mass energies were stable throughout most of the data-collection period.